Book Cafe Online Reservation System for Dino Bookcafe - Mohd Roseli, Nurul Amani; Hamid Ali, Firkhan Ali (Applied Information Technology And Computer Science, 2024)
DinoBook Cafe, a place that combines books and coffee, is improving its reservation system to address issues with the current manual method. The new web-based system aims to improve the customer experience by allowing easy table reservations, real-time table availability checks and event updates. The system, designed for multiple devices and browsers using HTML5, CSS3, JavaScript 4.0 and PHP, will replace manual systems to improve staff and customer satisfaction. Key features include user registration, easy booking management, digital menu, admin panel for customer management. The project anticipates increased productivity, fewer booking errors and better customer satisfaction and loyalty, positioning DinoBook Cafe as a leader in digital transformation in the cafe sector.